Regulation of tetrapyrrole biosynthesis in higher plants. (1st August 2005) - Moulin, M.; Smith, A.G.
Abstract : Plant tetrapyrroles are the most abundant biomolecules on the earth and are cofactors of many apoproteins essential for plant function. The four end-products sirohaem, chlorophyll, haem and phytochromobilin are synthesized by a common branched pathway, which is tightly regulated to ensure a continuous supply to the cognate apoproteins. This may induce strong competition between different branches of the pathway for common substrates. In addition, the intermediates, which are phototoxic, must not be allowed to accumulate in the cell. The major control points are during the synthesis of the initial precursor, ALA (5-aminolaevulinic acid), and at the branch points for the insertion of metal ions into the porphyrin macrocycle. A recent study has also suggested that tetrapyrroles are involved in the communication between the chloroplast and the nucleus, strengthening the necessity for tight regulation. However, intermediates remain difficult to quantify mainly due to their low content and the different properties of the intermediates. In this paper, we summarize the regulation of this pathway and we detail why it is important to have an accurate method for the determination of tetrapyrroles in plants.